Трехстороннее военное сотрудничество Турции, Грузии и Азербайджана (ноябрь 2012 г. - май 2016 г.) (Թուրքիայի, Վրաստանի և Ադրբեջանի միջև եռակողմ ռազմական համագործակցությունը (2012 թ. նոյեմբեր – 2016 թ. մայիս)) - Դավթյան Էրիկ (YSU Journal of International Affairs, 2016)
The paper aims at researching the main components of Turkey-Georgia-Azerbaijan trilateral military cooperation in the aforementioned period. Based on the analysis of main developments it is concluded that despite the considerable progress the trilateral cooperation has been of limited nature. The research defines the foreign policy goals that Turkey, Georgia and Azerbaijan have pursued through trilateral military cooperation.